Рідкісні види флори Національного природного парку "Білоозерський" - Крецул, О.А. (Український ботанічний журнал, 2011)
Приводится общая характеристика недавно созданного Национального природного парка «Белоозерский». Отмечены новые местонахождения пяти редких видов флоры парка, занесенных в третье издание «Червоної книги України» (Salvinia natans (L.) All., Epipactis hel leborine (L.) Crantz, Liparis loeselii (L.) Rich., Iris sibirica L., Stipa capillata L.). Дана краткая характеристика их местообитаний. General description of the recently established Biloozersky National Nature Park is given. New localities for 5 rare species listed in the third edition of the Red Data Book of Ukraine are added. The habitats and short population characteristics for Salvinia natans (L.) All., Epipactis helleborine (L.) Crantz, Liparis loeselii (L.) Rich., Iris sibirica L. and Stipa capillata L. are provided.